(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
In accordance with modern requirements, it provides for the development of professional knowledge, skills and qualifications of pedagogical staff of secondary schools, systematic improvement of their professional competence. Aimed on the formation of knowledge, skills, qualifications and competencies in order to improve the quality of education.